2020
DOI: 10.1186/s12998-020-00315-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Councils on Chiropractic Education expectations of chiropractic graduates changing for the better: a comparison of similarities and differences of the graduate competencies of the Chiropractic Council on Education-Australasia from 2009 to 2017

Abstract: Background: The Council on Chiropractic Education Australasia (CCE-A) is tasked with assessment and accreditation of chiropractic programs (CPs) in the Australasian community. To achieve this process the CCE-A has developed educational standards and graduate competencies which include minimum expectations of graduates prior to entry into the workforce. We sought to explore if these are changing overtime, and if so are these changes for the better. Method: The CCE-A 2009 and 2017 Competency Standards were locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In both the US and Canadian studies, the chiropractors were relatively older and had more years in practice than our sample. This is an important point of difference, as our analysis revealed that years in practice was negatively associated with EBP use; probably because more recently completed chiropractic education programmes are more likely to incorporate content on evidence-based practise [ 25 , 26 ].On the other hand, our analysis indicated that being older was significantly associated with higher use of EBP, which does appear somewhat contradictory. Although there is no clear explanation for this paradox, it is possible that the small number of chiropractors in our sample aged 60 years or above, could have been behaviourally different than the population of chiropractors in this age group, and thus, may not be representative of chiropractors aged 60 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…In both the US and Canadian studies, the chiropractors were relatively older and had more years in practice than our sample. This is an important point of difference, as our analysis revealed that years in practice was negatively associated with EBP use; probably because more recently completed chiropractic education programmes are more likely to incorporate content on evidence-based practise [ 25 , 26 ].On the other hand, our analysis indicated that being older was significantly associated with higher use of EBP, which does appear somewhat contradictory. Although there is no clear explanation for this paradox, it is possible that the small number of chiropractors in our sample aged 60 years or above, could have been behaviourally different than the population of chiropractors in this age group, and thus, may not be representative of chiropractors aged 60 years or older.…”
Section: Discussionmentioning
confidence: 99%